1989
DOI: 10.1203/00006450-198911000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Platelet-Activating Factor and Thromboxane in Group B Streptococcus-Induced Pulmonary Hypertension in Piglets

Abstract: ABSTRACT. Platelet-activating factor causes pulmonary hypertension, shock, hypoxemia, neutropenia, and increased pulmonary vascular permeability; some of its effects are due to thromboxane Az release. Evidence for a possible role of these mediators in the genesis of group B Streptococcus (GBS)-induced pulmonary hypertension was sought using specific receptor antagonists for PAF and thromboxane Az (TxA2) in anesthetized, ventilated piglets (5 12 d of age; n = 22). Infusion of 1 x 10' GBS/kg/min for one hour res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In many LPS lungs, target flows were not achieved. The increase in PVR during the ex-vivo phase can be explained by sustained vasoconstriction caused by prolonged action of endothelin, thromboxane and platelet activating factor 18,19 . The net effect of this generalized vasoconstriction in the lungs in the LPS group culminated in hypoxia of cells and deterioration of lung metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In many LPS lungs, target flows were not achieved. The increase in PVR during the ex-vivo phase can be explained by sustained vasoconstriction caused by prolonged action of endothelin, thromboxane and platelet activating factor 18,19 . The net effect of this generalized vasoconstriction in the lungs in the LPS group culminated in hypoxia of cells and deterioration of lung metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,24,25 Pulmonary hypertension has been linked to generation of the arachidonic acid metabolite TXA2 ' and selective TXA2 synthesis inhibitors as well as cyclooxygenase inhibitors have been shown to ameliorate these sequelae. 24,25,27,28 Another mediator implicated in the pathogenesis of these septic syndromes is TNF. The importance of TNF in septic shock has been shown using neutralizing antibodies against TNF that prevent endotoxic shock and in art sepsis sequelae due to Gram-negative bacteremia.…”
Section: Pretreatment With Gbs or Rtnfamentioning
confidence: 99%
“…Thromboxane seems to play a major role in sepsis. In experimentally induced streptococcal infections it was observed that cycloxygenase inhibitors, such as indomethacin, can prevent pulmonary hypertension [ 34 ]. Recent studies have revealed that vasoconstriction can also be determined by some phospholipids (in particular, phosphatidyl-glycerol and cardiolipin) present in the bacterial wall of streptococcus B [ 35 ].…”
Section: Introductionmentioning
confidence: 99%